Implemetasi Program UMKM dalam Pengentasan Kemiskinan di Desa Padengo Kabupaten Pohuwato - Mohamad, Sintia; Saleh, Gretty Syatriani; Umuri, Hasman (PROVIDER JURNAL ILMU PEMERINTAHAN, 2024)
This research discusses the implementation of the Micro, Small and Medium Enterprises (UMKM) program in efforts to alleviate poverty in Padengo Village, Pohuwato Regency. Padengo Village is one area that still faces significant challenges related to poverty. In this context, the UMKM program is one of the strategies adopted by the Padengo Village Government to improve community welfare and reduce poverty levels. This research uses a qualitative approach by collecting data through in-depth interviews with various stakeholders, including government officials, UMKM business owners, and local community members. Data was also obtained through direct observation and documentation studies. The results of the research show that the implementation of the UMKM program in Padengo Village has had a positive impact on poverty alleviation efforts. These programs have encouraged local economic growth, created new jobs, and provided training and support for UMKM to improve their skills and productivity. However, this research also identified several challenges and obstacles faced in implementing UMKM programs, including bureaucracy complex issues, lack of access to capital and markets, and lack of understanding of the benefits and opportunities of the UMKM program among the community. Based on these findings, several recommendations are proposed to increase the effectiveness of the UMKM program in alleviating poverty in Padengo Village. Among other things, simplifying administrative procedures, increasing access to capital and markets, participatory approaches in program planning and implementation, as well as increasing public understanding and awareness of the importance of UMKM in overcoming poverty.